2022
DOI: 10.3389/fimmu.2022.876291
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Tricky Cellular and Molecular Interactions in Pancreatic Tumor Microenvironment: New Food for Thought

Abstract: Pancreatic ductal adenocarcinoma (PDAC) represents 90% of all pancreatic cancer cases and shows a high mortality rate among all solid tumors. PDAC is often associated with poor prognosis, due to the late diagnosis that leads to metastasis development, and limited efficacy of available treatments. The tumor microenvironment (TME) represents a reliable source of novel targets for therapy, and even if many of the biological interactions among stromal, immune, and cancer cells that populate the TME have been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 249 publications
0
7
0
Order By: Relevance
“…The current situation in clinical oncology is that PDAC remains among the diseases with the most urgent and prevalent medical needs. However, several therapeutic options have been performed, entering clinical trials as combination treatments [ 82 ]. It is expected that translational research focused on understanding the complicated connections among single cells, such as CAF in the TME, is increasingly valuable to innovate novel treatment approaches [ 82 ].…”
Section: Diagnosis Through Methods Other Than Dna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The current situation in clinical oncology is that PDAC remains among the diseases with the most urgent and prevalent medical needs. However, several therapeutic options have been performed, entering clinical trials as combination treatments [ 82 ]. It is expected that translational research focused on understanding the complicated connections among single cells, such as CAF in the TME, is increasingly valuable to innovate novel treatment approaches [ 82 ].…”
Section: Diagnosis Through Methods Other Than Dna Sequencingmentioning
confidence: 99%
“…However, several therapeutic options have been performed, entering clinical trials as combination treatments [ 82 ]. It is expected that translational research focused on understanding the complicated connections among single cells, such as CAF in the TME, is increasingly valuable to innovate novel treatment approaches [ 82 ]. Recent studies revealed the heterogeneity of CAF, including myCAFs and iCAFs, and antigen-presenting CAFs (apCAFs), which show major histocompatibility complex II (MHC II) family genes, as an attractive target for immune therapy [ 83 ].…”
Section: Diagnosis Through Methods Other Than Dna Sequencingmentioning
confidence: 99%
“…The transitioning functions of neutrophils in humans are regulated by a minimum of seven chemokines (CXCL1, CXCL2, CXCL3, CXCL5, CXCL6, CXCL7, and CXCL8 [IL‐8]) and two receptors (CXCR1 and CXCR2). Specifically, neutrophils express the CXC receptors CXCR1 and CXCR2, which interact with CXC family chemokines released by tumour sources [25]. The concentration gradient of the CXCR2 ligand induces neutrophil migration toward PC, directing them from lower to higher concentrations [26].…”
Section: Transition Of Neutrophils To Tansmentioning
confidence: 99%
“…It is important to note that this subtype only accounts for 0-2.00% of PDAC patients ( 9 ). PDAC has a unique tumor microenvironment (TME) where various cells (mainly tumor cells, endothelial cells, immune cells, fibroblasts, nearby matrix, and microvessels) and substances (mainly cytokines, chemokines) interact to form a complex crosstalk network ( 10 , 11 ). As the tumor progresses, some components of the TME may shift from inhibiting tumor growth to promoting it.…”
Section: Introductionmentioning
confidence: 99%